The lexicon of Greek personal names and classical web services - Matthews, E; Rahtz, S (Insitute of Classical Studies, 2013)
This chapter documents the data resources of the long-term classical research project, The Lexicon of Greek Personal Names (LGPN), published in six volumes since 1987. It explains and demonstrates the web interfaces and services which now make available online the bulk of the LGPN, providing both powerful searching tools for scholars and an interface to allow other systems to link to LGPN data. Making the data available online provides direct, unmediated access to the material and supports exploitation of the data for further research both individual and collaborative. We describe the work that went into creating the Lexicon, detail the granularity of the data structures, and explain the history of the project's record management. We then move onto the work undertaken in recent years to provide an archival XML-based format for the Lexicon's long-term preservation, and show how this has allowed us to build new web services, including exposure of Resource Description Framework (RDF) metadata, using the ontology of the CIDOC Conceptual Reference Model (CRM) ontology for semantic web applications.